Role of Saccharomyces Probiotic in Addressing Heat Stress in Broiler Chickens - Abdelalim F Abd elalim (The International Journal of Multiphysics, 2024)
Application of natural feed additives with a view to enhance production performance, carcass quality and state of health has constituted an important request in production of poultry especially under heat stress conditions. This study aimed to investigate the impacts of dietary supplementation of Saccharomyces cerevisiae on growth performance parameters, some blood biochemical findings, antioxidant status in growing broilers exposed to heat stress. For this purpose, a total of 80 one-day-old chicks were randomly allotted into 4 dietary groups with 20 chicks each, which were fed for 35 days with a basal diet., Group1 served as the negative control group unexposed to heat stress (21-22 °C). While, Group 2 served as the positive control group exposed to heat stress (33-35 °C).While, Groups 3 un exposed to heat stress and supplemented with Saccharomyces cerevisiae (SC) and Groups 4 served as experimental groups exposed to heat stress (33-35 °C) and supplemented with Saccharomyces cerevisiae (SC). respectively The obtained results showed that SC dietary supplementation to basal diet in groups T3, T4 resulted in improved growth performance parameters (increased final B.W, BWG, F.C and F.C.R), improved liver and kidney function (reduced serum AST, ALT, creatinine and uric acid level), improved protein level (total protein& albumin & globulin), improved antioxidant status (reduced serum MDA levels, Cortisol and increased serum CAT, SOD, TAC and GPx activities), increase antibody titer against IB& ND, decrease level of glucose, PH, Haptoglobin, CRP. as compared to birds in group 2.